EXTRATION OF PHENOLIC COMPOUND FROM NEPHELIUM LAPPACEUM LEAVES FOR THE TREATMENT OF DIABETES - KHAN, SAIMA (2014)
There has been an enormous attention in development of unconventional medicines for the treatment of Type 2 diabetes, precisely selection for phytochemicals with the capability to postponement or inhibit glucose absorption. Phenolic compound from Nephelium lappaceum leaves was investigated using Gallic acid as a precursor. The phenolic compound was extracted in 50, 70, 90 and 100% ethanol, methanol, isopropanol and acetone with solid to solvent ratio (10:1 w/v ratio) at 45°C, 60°C and 75°C. The aim of present study was to provide in-vitro confirmation for potential inhibition by FRAP assay, ABTS assay, a-amylase assay and a-glucosidase assay. Characterization of Nephelium Lappaceum Green and Brown leaves was taken in account. The percentage of moisture content was 33.14%o in semi-dried Brown leaves and 51.24% in fresh Green leaves.